2020
DOI: 10.1002/ett.3860
|View full text |Cite
|
Sign up to set email alerts
|

TD‐PSO: Task distribution approach based on particle swarm optimization for vehicular ad hoc network

Abstract: The rapid advancement of the artificial intelligence revolution during the past decade has significantly affected vehicular ad hoc networks (VANETs). Several applications have been introduced that must meet the requirements of a VANET, including automatic driving and preaccident alerts and broadcasting of video.The customization of vehicles for implementation of these applications is costly and might not be possible due to many constraints, particularly resource limitations. In order to achieve compliance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Results have demonstrated that PSO can achieve nearoptimal beamforming solutions. Considering vehicular adhoc networks, a task-distribution PSO is proposed to efficiently distribute tasks among vehicles that belong to the same cluster [228]. The results shows that the proposed PSO scheme outperforms GA in terms of overhead reduction while its overhead performance is comparable with linear programing.…”
Section: B Wireless Communicationsmentioning
confidence: 99%
“…Results have demonstrated that PSO can achieve nearoptimal beamforming solutions. Considering vehicular adhoc networks, a task-distribution PSO is proposed to efficiently distribute tasks among vehicles that belong to the same cluster [228]. The results shows that the proposed PSO scheme outperforms GA in terms of overhead reduction while its overhead performance is comparable with linear programing.…”
Section: B Wireless Communicationsmentioning
confidence: 99%
“…Using real-world traces to model the mobility of edge servers, the PSO is shown to have lower service latency than the linear programming method when the quality is relaxed, but it is not preferred to use when the quality requirement becomes stricter. The computation offloading problem is also investigated in many other studies [123]- [125]. For example, to support latency-sensitive applications on the Internet of vehicles (IoV), the work in [124] considers combining software-defined networking (SDN) and edge computing, and proposes a holistic architecture.…”
Section: B Computation Offloadingmentioning
confidence: 99%
“…In partial encryption IoT devices encrypts the data with only dummy attribute and delegate most of CP-ABE cryptography operations to EPS server. Several schemes proposed this idea such as the scheme proposed in [12,24,25]. The details of full and partial encryption will discuss later in this section.…”
Section: The Proposed Schemementioning
confidence: 99%